The First Report of Panaeolus Olivaceus and Panaeolus Guttulatus from Iran - Elham Seidmohammadi; Saeed Abbasi; Mohammad Reza Asef (تاکسونومی و بیوسیستماتیک, 2019)
During macrofungal surveys continually undertaken from 2014 to 2017 at different locations of Eslamabad-e Gharb and Gilan-e Gharb, Kermanshah Province, a large number of agaric fungi including two specimens belonging to the genus Panaeolus were collected. At the collection site, while recording geographical coordinates, habitat characteristics, growth patterns, and macroscopic morphological features were recorded and photographed. Microscopic features including basidiospores, basidia, and cystidia were observed, measured, and illustrated using a light microscope, OLYMPUS BX51. Also, the DNA sequence of the rDNA-ITS region was amplified and sequenced using ITS1 and ITS4 primers. The phylogenetic analysis and the determination of species relationships were performed by the Maximum Likelihood method with 1000 repetitions of 1000 bootstrap replicates using the MEGA6 software. Based on the results obtained from morphological examinations along with data obtained from ITS- rDNA sequences, two species including Panaeolus olivaceus and Panaeolus guttulatus were identified. According to the literature, both species were new records for mycobiota of Iran. In the present paper, the morphological description of the mentioned species is presented.